Vehicle of erotic liberation or instrument of career survival? Japan's ideologies of English as reflected in conversation school advertisements. (October 2019) - Nuske, Kyle
Abstract: Private, for-profit English conversation schools ( eikaiwa ) are a prominent venue of study among Japanese adults. Thus, eikaiwa marketing strategies are reflective and constitutive of discourses that structure the desire or compulsion for English learning in Japan. Synthesizing critical, multimodal, and Foucauldian discourse analysis techniques, this study examines 28 recent print eikaiwa advertisements to explicate the visual and verbal elements through which particular ideologies of English proficiency and its benefits are constructed. Findings are integrated with data from a small-scale survey of Japanese adults (n = 13) to illuminate how the advertisements are perceived by members of the target audience. Whereas these advertisements have historically exploited images of Caucasian men to incite heterosexual women's akogare (yearning), texts in the present corpus commonly frame English learning as a rational process of acquiring quantifiable skills, which enhance workers' self-worth by ensuring their continued value to their employers. Moreover, they often characterize English study as rigorous and inevitable albeit burdensome and demeaning. The study argues that these emerging themes are attributable to the growing influence of neoliberal ideologies and practices, and they mainly serve to propagate fantasies of English proficiency as a reliable means of obtaining stable vocations within volatile labor markets.